"Did That Play of Mine …?": Theatre, Commemoration and 1916. (16th January 2018) - Richards, Shaun
Abstract: W.B. Yeats's question 'Did that play of mine send out/Certain men the English shot?' from 'The Man and the Echo' (1938), speculatitively postions his play, Cathleen ni Houlihan (1902), as the driving force behind the Easter Rising of 1916. While theatre was a powerful factor in creating the cultural-politial climate which gave birth to the Rising, Yeats's question disingenously gives his play an exclusive influence on events when other playwrights, specifically Patrick Pearse and Thomas MacDonagh, who actually led the Rising, had a far better claim to being its dramatic inspiration. This article considers the theatrical influences on the Rising, examining Cathleen ni Houlihan and other plays of the period, and outlines the production history of Yeats's play as an indication of its post-Rising status, comparing it to that of Sean O'Casey's play about the Rising, The Plough and the Stars (1926).